(untitled) (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2015)
Total quality management (TQM) is often considered a vital antecedent of a firm’s performance. However, not much is known about the mechanism through which TQM helps organizations to create this performance. The incorporation of organizational learning capability in the goals and objectives of TQM may help us understand TQMperformance relationship. This study focuses on the interrelationship among TQM practices, organizational learning capability and organizational performance in textile sector of Pakistan. Moreover, this study also investigates organizational learning capability as a mediator between TQM practices and organizational performance. The results are based on the empirical data collected from a self-administrative survey from 270 managers working in 90 organizations of the textile sector. Hierarchical linear modeling is used to examine the hypothesized relations. The results reveal that both TQM practices and organizational learning capability of the manufacturing firms significantly impact their performance. The mediating role of organizational learning capability between TQM-performance is fully supported by our data. The implications for the theory and practice are discussed along with direction for the future research.